THE EFFECT OF PLACE IDENTITY, PLACE IMAGE AND RESIDENTS WELCOMING TOURISTS ON ATTITUDES TO POSITIVE IMPACTS OF TOURISM - Çigdem Unurlu (Enlightening Tourism: A Pathmaking Journal)
This study aims to identify residents’ attitudes regarding place image, place identity and residents welcoming tourists, and determine the effect of these attitudes on attitudes to positive impacts of tourism. Result of the analyses reveal that place identity has a significant effect on attitudes to positive impacts, on residents welcoming tourists and on place image. Also, it was concluded that residents welcoming tourists has a significant effect on attitudes to positive impacts, and place image has a significant effect on residents welcoming tourists.